Identification of physiological traits at seedling stage associated with salt tolerance in wheat variety KH 65 using RILs - Devi, Rajni; Ram, Sewa; Verma, Ajay; Pande, Veena; Singh, Gyanendra Pratap (Journal of Cereal Research, 2018)
Salinity is a major stress affecting production and productivity of wheat across the world. Understanding physiological traits associated with salt tolerance can help in breeding for improving wheat under salt stress. In the present investigation, physiological traits in 3rd leaf at seedling stage and grain yield at maturity were studied in a population of RILs derived from a cross between salt tolerant (Kharchia 65) and susceptible (HD 2009) cultivars under control (pH8.2) and sodic condition (pH 9.2) in microplots. Though HD 2009 had higher yield under control conditions, it exhibited a higher reduction in yield (44.7%) under sodic stress as compared to KH 65 (9.8%). There was a significantly lower accumulation of Na+ content and higher accumulation of K+, proline and chlorophyll content in the 3rd leaf of KH 65 as compared to HD 2009 under sodic stress. Na+ content exhibited significant negative correlation (P